Economic and legal aspects of the formation Kazakh model of health (Journal of actual problems of jurisprudence, 2019)
In this article are considered questions of economic and legal regulation in the health system, directed onimplementation of the major or important social programs in Republic of Kazakhstan in modern period of time. Theanalysis of governmental activities, their purposes and tasks in the health care system is carrying.Key words: health system, nation health, social protection, health system.